Heart of Borneo Series 6: Checklist of Plants of Lanjak Entimau Wildlife Sanctuary - Meekiong, Bin Kalu; Yahud, Wat; Mohd Effendi, Bin Wasli; Mohd Shahbudin, Sabki; Hashimah, Binti Elias; Shirley, Chip; Mogeret, Binti Sidi; Pau, Madline George; Zinnirah, Shabdin; Yazid, Kalbi (Forest Department Sarawak, 2019)
The Heart of Borneo (HoB) Initiative is a voluntary transboundary cooperation between Brunei, Indonesia and Malaysia. The Declaration was signed on February 2007. The project aims to protect the biological, ecological, cultural richness and as well as for conservation of rainforest of Borneo. In Sarawak, the HoB covers 2.689 million ha over a contiguous block along Sarawak’s boundaries with Kalimantan, Sabah and Brunei. The HoB is fully in line with existing policies by both state and federal government. The HoB focusing on three key elements; people welfare, biodiversity conservation and protection of environment based on five pillars, (1) sustainable forest management, (2) ecotourism-based on cultural, adventure and nature, (3) conservation of biological diversity, (4) sustainable landuse, and (5) community-based poverty eradication program. This plants checklist book is our six serial from the Heart of Borneo Series in conjunction with the scientific expedition conducted in Lanjak Entimau Wildlife Sanctuary in 2008 and data from the past research conducted in the areas.